Highest and Best Use Analysis for an Apartment with Office Buildings or Shopping Centers in East Surabaya - Barca Hadi Juwono; Timoticin Kwanda; Njo Anastasia (Advances in Civil Engineering and Sustainable Architecture, 2019)
Surabaya is the capital of East Java and the center of communityactivities. A developer has a plan to build a residential area in East Surabaya,located on Dharma Husada Indah Barat III road with an area of 7.123 m2. Afterconsidering many aspects, there are two alternative ideas that really attract theattention of this developer, namely, apartments with office buildings or apartmentswith shopping centers. The best decision results of the two alternatives can beanalyzed through the highest and best use (HBU) analysis method. The HBU mustfulfill four criteria, that is, legally permissible, physically possible, financiallyfeasible, and maximally productive. Of the two scenarios, the one that meets theHBU aspect is an apartment with office buildings, with the annual internal rate ofreturn of 99%, the net present value of Rp. 563.448.604.512,- with payback period60,46 months and discounted payback period 60,8 months.